Pharmacology for anaesthesia and intensive care - Peck, Tom; Harris, Benjamin (Consultant Anaesthetist) (Cambridge University Press, 2021)
"The art of anaesthesia includes many different facets deeply rooted in medical behaviour: listening and talking to the patient, evaluating, diagnosing and taking the right decisions. Drugs are central to patient care in many areas of medical practice and the anaesthetist as well as all healthcare practitioners need to have a clear understanding of therapeutics. However, competence in anaesthetic management during the whole perioperative management of our patients implies good knowledge of pharmacology; it is the bread and butter of our profession. The dynamic nature of drug development in this field compels a continuous updating of the characteristics of drugs that form such an essential part of our armamentarium"--